2014
DOI: 10.1002/cbic.201300799
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching Reveals Heterogeneous Stoichiometry for Equinatoxin II Oligomers

Abstract: Equinatoxin II (EqtII), a sea anemone cytolysin, is known to oligomerize to form pores that spontaneously insert into membranes. Crystallographic and cryo-EM studies of structurally similar cytolysins offer contradictory evidence for pore stoichiometry. Here we used single-molecule photobleaching of fluorescently labeled EqtII to determine the stoichiometry of EqtII oligomers in supported lipid bilayers. A frequency analysis of photobleaching steps revealed a log-normal distribution of stoichiometries with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 51 publications
2
23
1
1
Order By: Relevance
“…Even though from our experimental data we cannot estimate what oligomeric state(s) would potentially be a functional unit for pore formation, mathematical modeling also suggests that tetramers are the most stable form of EqtII in the membrane, in agreement with recent determination of the stoichiometry of EqtII oligomers in supported bilayers (33), the structure of Sticholysin II in monolayers (13), and contrary to the models based on higher oligomeric species proposed for Fragaceatoxin C (15). However, one essential difference with structural studies reported so far is the detection of multiple coexisting oligomeric forms, which underscores the power of our single molecule approach when studying dynamic processes.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Even though from our experimental data we cannot estimate what oligomeric state(s) would potentially be a functional unit for pore formation, mathematical modeling also suggests that tetramers are the most stable form of EqtII in the membrane, in agreement with recent determination of the stoichiometry of EqtII oligomers in supported bilayers (33), the structure of Sticholysin II in monolayers (13), and contrary to the models based on higher oligomeric species proposed for Fragaceatoxin C (15). However, one essential difference with structural studies reported so far is the detection of multiple coexisting oligomeric forms, which underscores the power of our single molecule approach when studying dynamic processes.…”
Section: Discussioncontrasting
confidence: 43%
“…Under these conditions, the number of particles per area was comparable for both mutants. Moreover, differences in concentration between both mutants are not expected to have significant effects on the kinetics of oligomerization or the formation of complexes as suggested by Baker et al (33).…”
Section: On the Cell Surface Eqtii Is Present As A Mixture Of Multiplementioning
confidence: 71%
“…In particular, sphingomyelin (SM) is a lipid that facilitates binding and pore formation (24), although this lipid is not strictly necessary to permeabilize model membranes (25). Once bound to the membrane, actinoporins oligomerize and transfer their N-terminal helical region toward the hydrophobic core of the membrane, although the exact sequence of events is still under debate (19,26,27). During the insertion step, the N-terminal ␣-helix spans the entire thickness of the membrane and lines the wall of the octameric pore as recently shown by x-ray crystallography (28).…”
mentioning
confidence: 99%
“…Intriguingly, membranes made of a single type of lipid are not susceptible to the lytic activity of the toxin (25,26,30). In contrast, mixtures of lipids containing SM and other lipids such as phosphatidylcholine (PC) or cholesterol often trigger pore formation.…”
mentioning
confidence: 99%
“…The toroidal pore model was initially proposed and is mainly based on functional studies with sticholysins and EqtII . Kinetic and electrophysiological studies and more recently single molecule imaging have revealed that predominantly 3‐4 monomers of these proteins form functional pores . Moreover, crystalografic data of a prepore like structure of StII in lipid monolayers shows that the units that form the assembly do not establish relevant protein–protein interactions .…”
Section: Introductionmentioning
confidence: 99%